2013
DOI: 10.1007/s11136-013-0453-2
|View full text |Cite
|
Sign up to set email alerts
|

Poor self-rated health associated with an increased risk of subsequent development of lung cancer

Abstract: Respondents who perceive their health as poor had an increased risk of developing lung cancer also after adjusting for smoking. This suggests that self-rated health reflects a broad range of factors important for development of this cancer type. Nevertheless, due to the explorative analysis of the specific cancer types, these findings need to be repeated before elaborate interpretations can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…Our main finding, that the perception of health in general over time is a risk factor for cancer later in life, is in line with the findings of a similar prospective cohort study of 25 532 participants [8]. In contrast to that large cohort study, we did not find an increased risk for lung cancer among people with poor SRH.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our main finding, that the perception of health in general over time is a risk factor for cancer later in life, is in line with the findings of a similar prospective cohort study of 25 532 participants [8]. In contrast to that large cohort study, we did not find an increased risk for lung cancer among people with poor SRH.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to that large cohort study, we did not find an increased risk for lung cancer among people with poor SRH. This discrepancy might be because of a heterogenic and older study population in the cohort study by Riise et al [8] and the selected, younger, and more homogenous study population in this study. Our results are supported by the findings of three prospective cohort studies of the association between SRH and the incidence of chronic diseases including cancer [10,11], although these studies had medium to small samples (N ¼ 4493, 4770, 783, respectively) and few cancer cases (N ¼ 102, 544, 60, respectively), making site-specific cancer risk analysis difficult.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It is a common indicator of health status, and despite the lack of a direct clinical evidence, it correlates with more complex health measures (24). Self-reporting has been employed as a morbidity (25,26) and mortality (27,) predictor. In this regard, the present study showed that health perception behaves as a risk indicator for experience and dental caries prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that SRH did not independently predict the incidence of cancer or other chronic diseases [17]. Although one large Norwegian study of 25,532 participants found an increased risk of lung cancer among individuals with poor SRH [18], the general impression from prospective studies does not seem to suggest that SRH plays an independent role in overall cancer causation. Regarding the role of QOL as a potential predictor of the risk of cancer, the issue is much less studied.…”
Section: Introductionmentioning
confidence: 58%